A quasi-solid-state high-rate lithium sulfur positive electrode incorporating Li10GeP2S12 - Boyi Pang; Huanxin Li; Yiming Guo; Bochen Li; Feiran Li; Huw C. W. Parks; Liam R. Bird; Thomas S. Miller; Paul R. Shearing; Rhodri Jervis; James B. Robinson (Communications Materials)
Abstract Lithium–sulfur batteries offer high theoretical energy density for advanced energy storage, but practical deployment is hindered by the polysulfide shuttle effect and sluggish kinetics in conventional catholytes. Here, we develop a high-rate sulfur cathode by integrating Li₁₀GeP₂S₁₂, a highly ion-conductive solid-state electrolyte, directly into the positive electrode. We systematically investigate the influence of solvent systems and binders on electrochemical performance, while optimising the slurry casting process. Electrochemical tests demonstrate that the addition of Li₁₀GeP₂S₁₂ improved lithium-ion transport, reduced internal resistance, and enhanced reaction kinetics, leading to a high initial capacity of over 1400 mAh g-1. We observe high-capacity retention at high current densities (1 C) with the positive electrode exhibiting a stable capacity of 800 mAh g-1, significantly outperforming control samples fabricated without Li₁₀GeP₂S₁₂. This study confirms that the integration of Li₁₀GeP₂S₁₂ into the positive electrode enhances the performance of quasi-solid-state lithium–sulfur batteries, offering potential for future improvements based on the optimisation of lithium-ion conducting pathways in the positive electrode